The lack of neuropeptide Y‐Y1 receptor signaling modulates the chemical and mechanical properties of bone matrix. Issue 3 (20th January 2020) - Sousa, Daniela M.; Martins, Pedro S.; Leitão, Luís; Alves, Cecília J.; Gomez‐Lazaro, Maria; Neto, Estrela; Conceição, Francisco; Herzog, Herbert; Lamghari, Meriem
Abstract: Genetic and pharmacological functional studies have provided evidence that the lack of Neuropeptide Y‐Y1 receptor (Y1 R) signaling pathway induces a high bone mass phenotype in mice. However, clinical observations have shown that drug or genetic mediated improvement of bone mass might be associated to alterations to bone extracellular matrix (ECM) properties, leading to bone fragility. Hence, in this study we propose to characterize the physical, chemical and biomechanical properties of mature bone ECM of germline NPY‐Y1 R knockout (Y1 R −/− ) mice, and compare to their wild‐type (WT) littermates. Our results demonstrated that the high bone mass phenotype observed in Y1 R −/− mice involves alterations in Y1 R −/− bone ECM ultrastructure, as a result of accelerated deposition of organic and mineral fractions. In addition, Y1 R −/− bone ECM displays enhanced matrix maturation characterized by greater number of mature/highly packed collagen fibers without pathological accumulation of immature/mature collagen crosslinks nor compromise of mineral crystallinity. These unique features of Y1 R −/− bone ECM improved the biochemical properties of Y1 R −/− bones, reflected by mechanically robust bones with diminished propensity to fracture, contributing to greater bone strength. These findings support the future usage of drugs targeting Y1 R signaling as a promising therapeutic strategy to treat bone loss‐related pathologies.